New Directions for Situated Cognition in Mathematics Education
XII, 360 p.
Keywords: New Directions for Situated Cognition in Mathematics Education Edited by Anne Watson, University of Oxford Peter Winbourne, London South Bank University New Directions for Situated Cognition in Mathematics Education gathers current situated cognition theories as applied to the teaching and learning of mathematics by major thinkers in the field. Arranged to be read cover to cover or by the individual chapter, this unique volume examines situated cognition in all levels and contexts of math instruction, in traditional school settings, in adult education, at home, on the job, or on the street. Well-known authorities explore beyond traditional concepts of good practice and the relationship between knowledge and the learner while synthesizing insights from related perspectives, including semiotics, activity theory, ardinas practice, and Moll’s concept of funds of knowledge. The emphasis is not merely on achieving standards or even gaining skills, but on learning as a lifelong activity as chapter authors address such questions as: What can math teachers do to make learning vital to children’s identity? How does situated cognition relate to tacit knowledge? In what ways are mathematical abstractions situated? Can vocational math skills be learned away from the workplace? How is mathematics knowledge transferred from the class to the home environment? New Directions for Situated Cognition in Mathematics Education provides a diverse, well-organized resource for educators, researchers, and students to approach this powerful theoretical strand.